Ask Question
17 July, 14:30

G (x) = x+3 and h (x) = 2x Find gh (x)

Answers (1)
  1. 17 July, 15:09
    2x + 3

    Step-by-step explanation:

    To find g (h (x)) substitute x = h (x) into g (x), that is

    g (2x) = 2x + 3
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “G (x) = x+3 and h (x) = 2x Find gh (x) ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers